Discrete Element Modeling of Crack Initiation Stress of Marble Based on Griffith’s Strength Theory - Suifeng Wang; Fei Tan; Minglong You; Yu-Yong Jiao; Fubin Tu (Advances in Civil Engineering)
Investigating the crack initiation stress of rocks is vital for understanding the gradual damage process of rocks and the evolution law of internal cracks. In this paper, the particle flow code method is used to conduct biaxial compression tests on a marble model with an elliptical crack under different confining pressures. According to the evolution status of microcracks in the rock during compression, four characteristic stresses are defined to reflect the gradual damage process of the marble. Two different methods are used to obtain crack initiation stress of rocks, and the calculation results are compared with those based on Griffith’s strength theory to verify the accuracy of this theory under compressive stress. Based on the numerical simulation results, the evolution law for the strength parameters of marble with the degree of damage is described. According to the proportional relationship between the peak stress and crack initiation stress, a new method for predicting the initiation stress is proposed, whose effectiveness is verified. Overall, the results of this study can serve as a useful guide for solving the important problems of slab cracking and rockburst encountered in underground space engineering.